Mutagenesis by retroviral insertion in chemical mutagen-generated quasi-haploid mammalian cells - Sung O. Kim; Soon-Duck Ha; Sangun Lee; Sarah Stanton; Bruce Beutler; Jiahuai Han (BioTechniques)
Diploidy is a major obstacle to the mutagenic analysis of function in cultured mammalian cells. Here, we show that 6–8 rounds of chemical mutagenesis generates quasi-haploid cells that can be used as targets for insertional mutagenesis using a specially designed retroviral vector that permits rapid identification of disrupted genes in each cell that bears a phenotype of interest. The utility of combined chemical and insertional mutagenesis is illustrated by the identification of novel host genes that are required for macrophage sensitivity to anthrax lethal factor.